Efek Pemberian PRF dengan Xenograft dan Alloplast terhadap Jumlah Osteoblas - Hansen Kurniawan (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2015)
Background: Bone graft materials have been widely used to regenerate bone defects, which are caused by trauma, tumor resection, pathological processes, and congenital bone defects. Type of bone graft is classified into several types, autograft, allograft, xenograft, and alloplast PRP and PRF derived from autologous blood which sends a high concentration of growth factors on bone defect area. Purpose: The aim of this study is to investigate the effect of PRF with xenograft and alloplast to osteoblast in bone New Zealand rabbits. Materials and Methods: The experiment was held by Post Test Group design. Twenty seven male New Zealand Rabbits were divided into three group. The first group performed the treatment on the right hind limb be treated with Alloplast and PRF treated, The second group performed the treatment on the right hind limb be treated with xenograft and PRF, and The third group was the control group performed the treatment on the right hind limb was given PRF. After treatment the rabbits were sacrificed. Osteoblast of each group was measured by EDTA method All data experiment were analyzed by ANOVA and LSD test (p<0,01). Results: The result of this study showed that the results of osteoblasts between PRF with alloplast compared with prf with xenografts, significant differences as a result of the process of bone formation to see the results of better bone formation. Conclusion: In PRF with alloplast has better results compared with PRF with xenografts from to increase osteoblasts expression.